Synthesis and Bioactivities of Novel 1,3,4-Thiadiazole Derivatives of Glucosides - Chen, Meihang; Zhang, Xun; Lu, Daowang; Luo, Hairong; Zhou, Zengyan; Qin, Xufeng; Wu, Wenneng; Zhang, Guoping (Frontiers in Chemistry, 2021)
A series of novel 1,3,4-thiadiazole derivatives of glucosides were synthesized by the starting materials d-glucose and 5-amino-1,3,4-thiadiazole-2-thiol in good yields with employing a convergent synthetic route. The results of bioactivities showed that some of the target compounds exhibited good antifungal activities. Especially, compounds 4i showed higher bioactivities against Phytophthora infestans (P. infestans), with the EC50 values of 3.43, than that of Dimethomorph (5.52 μg/ml). In addition, the target compounds exhibited moderate to poor antibacterial activities against Xanthomonas oryzae pv. oryzae (Xoo), Xanthomonas campestris pv. citri (Xcc).